Pengaruh Electronic Word of Mouth (eWOM) terhadap Intensi Pembelian Produk Pakaian Bekas pada Live Streaming TikTok - Riyanti, Selly Dwi; Oktarisa, Fidia (Lembaga Yasin AlSys, 2025)
The rising trend of purchasing second-hand clothing (thrifting) through social media, particularly via TikTok's live streaming feature, has led consumers to rely heavily on reviews and comments as primary sources of information in their decision-making processes. This study aims to analyze the influence of Electronic Word of Mouth (eWOM) on purchase intention for second-hand clothing via TikTok live streaming. A quantitative causal approach was employed, with a population comprising Indonesian consumers who have previously purchased second-hand clothing through TikTok. The sample consisted of 399 respondents selected using purposive sampling. Data were collected using an eWOM scale adapted from Hasibuan (2024), based on the theoretical framework of Lin, Wu, and Chen (2013), and a purchase intention scale modified from Fristasari (2019), grounded in Ajzen’s (2005) theory. The analysis revealed that eWOM has a significant influence on purchase intention, contributing 40.4% to the variance (sig = 0.000; R² = 0.404). These findings indicate that the more positively consumers perceive reviews and comments, the greater their tendency to purchase second-hand clothing through TikTok live streaming. The study underscores the importance of consumer review–driven digital communication strategies as an effective marketing approach in the social media era.